Use of information and communication technologies (ICT) and its relationship with the formation of attitudes towards the environment in the "Leoncio Prado" military public educational institution. - Vicente Jauregui, Susana Cecilia (2021)
The study was extended analyzing methodological frameworks, background and experiences that support the various concerns and proposals currently being discussed, such as incorporating ICT and the environmental approach to education, and was raised as Purpose to analyze the relationship between the "use of ICT"; Considering its dimensions, knowledge and mastery of ICT, the general use of ICT in the school context and the pedagogical flexibility to use ICT in the classroom; With the "formation of attitudes towards the environment" in the field of secondary basic education. The research was carried out from a quantitative approach of descriptive correlational scope, considering as a sample of study to 200 students of secondary education of the military public educational institution "Leoncio Prado" of Lima, Peru. Information was collected with valid and reliable surveys, which was analyzed statistically at a descriptive, correlational level and with evidence of hypothesis. It highlights in the results, the variability in the knowledge and domains that teachers have in the use of ICT, evidence of a general use of ICT and below the levels of dominance that teachers have; A partial level of student satisfaction with respect to the formation of attitudes towards the environment at school; Lack of relationship between ICT dominance and the formation of attitudes towards the environment of students; Significant relationship between the form of use of ICTs and pedagogical flexibility in the use of ICT, with the formation of attitudes towards the environment. Sufficient evidence was presented to help corroborate the study hypothesis that affirm the significant relationship between the use of ICTs and the formation of attitudes towards the environment.